Effect of colchicine derivatives on the antibody response induced in vitro - Sterzl, J; Santavý, F; Sedmera, P; Cudlín, J (Folia microbiologica, 1982)
Effect of 44 colchicine derivatives on the induction of antibody response in tissue cultures was tested. Lymphatic cells from the spleen of BALB/c mice were cultivated with antigen (sheep red blood cells) and the number of antibody forming cells was determined by the plaque technique. Most compounds with the immunoinhibitory effect are derived from the colchicine formula (I). The effect was increased by introducing ethyl, formyl or methylenedioxide groups. Colchinols exerted very good immunoinhibitory effect resulting by contraction of tropolone ring C into the aromatic one. A complete loss of the effectivity was detected in the case of glucoside of colchicine, colchiceine, isocolchicine, oxycolchicine, allocolchicine and in lumiderivatives of colchicine. No correlations between the immunoinhibitory effect, toxicity and stathmokinetic effect were detected: decrease of cell viability and arrest of mitoses were not observed in cultured lymphocytes within the range of the immunoinhibitory effect. The effect of colchicine derivatives was manifested as the inhibition of lymphocyte blastogenesis, which is probably the result of membrane transport blockade.
Keywords: Mice; Mice, Inbred BALB C; vztahy mezi strukturou a aktivitou; Female; Antibody Formation; Cells, Cultured; Animals; myši; ženské pohlaví; myši inbrední BALB C; lymfocyty; Lymphocytes; zvířata; Structure-Activity Relationship; kultivované buňky; kolchicin; Colchicine; tvorba protilátek